2018
DOI: 10.1016/j.chempr.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Grain-Boundary Functionalization for High-Efficiency Perovskite Solar Cells with Exceptional Stability

Abstract: Grain boundaries in polycrystalline thin films of hybrid perovskites can play a key role in determining the performance and stability of perovskite solar cells. Here, we demonstrate the controlled, continuous grain-boundary functionalization of hybrid perovskite thin films with a rationally selected triblock copolymer with dual hydrophobic-hydrophilic functionalities. This unique grain-boundary structure is responsible for the enhanced optoelectronic properties and environmental stability of these thin films. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(159 citation statements)
references
References 38 publications
6
153
0
Order By: Relevance
“…In this system, we anticipate that the first Ag atoms are able to diffuse across the smooth surfaces of the perovskite crystal grains as usual, however, become stuck and preferentially settle at the grain boundaries, where the crevasses allow stronger interaction between Ag and MA + or I − in the MAPbI 3 perovskite phase. After the initial Ag atoms settle, additional Ag atoms accumulate and self‐assemble along the grain boundaries into the observed crescent shapes; similar crescent shapes of Ag NPs have been described by Padture and co‐workers . A schematic diagram showing this mechanism is included in the Figure S1, Supporting Information.…”
Section: Resultssupporting
confidence: 71%
“…In this system, we anticipate that the first Ag atoms are able to diffuse across the smooth surfaces of the perovskite crystal grains as usual, however, become stuck and preferentially settle at the grain boundaries, where the crevasses allow stronger interaction between Ag and MA + or I − in the MAPbI 3 perovskite phase. After the initial Ag atoms settle, additional Ag atoms accumulate and self‐assemble along the grain boundaries into the observed crescent shapes; similar crescent shapes of Ag NPs have been described by Padture and co‐workers . A schematic diagram showing this mechanism is included in the Figure S1, Supporting Information.…”
Section: Resultssupporting
confidence: 71%
“…In previous works, there have been several attempts to apply polymeric additives to perovskite solar cells. [ 29–38 ] For example, Zuo et al demonstrated that the incorporation of poly (4‐vinylpyridine) additives into the perovskite film is an effective strategy to improve both the device efficiency and the stability. [ 23 ] Bi et al utilized poly(methyl methacrylate) as a template to control perovskite nucleation and crystal growth and fabricated solar cells with PCE up to 21.6%.…”
Section: Figurementioning
confidence: 99%
“…Zong et al. reported an effective modification method for grain‐boundary . By introducing a triblock copolymer, consisting with hydrophilic‐hydrophobic‐hydrophilic symmetric structure, they successfully achieved ultra‐smooth perovskite films with grain‐boundary regions that were continuously functionalized and the resulting PSCs demonstrated enhanced opto‐electronic performance and environmental stability simultaneously.…”
Section: Stability Challengesmentioning
confidence: 99%
“…Besides, research on all-inorganic PSCs, in which organic components MA + and FA + are totally replaced by inorganic Cs + cations, is the current hotspot, thanks to the superior stability of inorganic material. [91,92] Liang et al fabricated CsPbBr 3 solar cells without any volatile organic components. [93] The whole process of fabrication could be carried out in ambient air while humidity control was unnecessary.…”
Section: Other Factors For Stabilitymentioning
confidence: 99%
See 1 more Smart Citation